THE TACTICAL GAMES MODELSAND MOTIVATION LEARNINGOF PHYSICAL FITNESS THE VOCATIONAL SCHOOL STUDENTS - Agi Ginanjar (Jurnal Kependidikan, 2018)
This study aims to determine differences in the physical fitness of students studying through tactical games model and students who learn through conventional learning model and to understand the interaction between the learning model with learning motivation towards physical fitness. The method used in this study is a research method experiment with a 2x2 factorial design, data collection techniques for motivation to learn using a questionnaire, to use the physical fitness Physical Fitness Test Indonesia's equivalent of high school and for hypothesis testing using ANOVA two ways. Participants in this study were students of SMK TKR NU Kaplongan Indramayu many as 276 people with a sample of 74 people, for the determination of the sample using Taro Yamane formula and sampling using simple random sampling.The results stated there are differences in the physical fitness of students studying through tactical learning model and students who learn through conventional learning modeland there is no interaction between the learning model with learning motivation towards physical fitness.MODEL PEMBELAJARAN TAKTIS DAN MOTIVASI BELAJAR TERHADAP KEBUGARAN JASMANI SISWA SMKAbstrakPenelitian ini bertujuan untuk mengetahui perbedaan kebugaran jasmani kelompok siswa yang belajar melalui model pembelajaran taktis dan kelompok siswa yang belajar melalui model pembelajaran langsung, serta interaksi antara model pembelajaran dengan motivasi belajar terhadap kebugaran jasmani.Metode yang digunakan dalam penelitian ini adalah metode penelitian true eksperimen dengan desain faktorial. Populsi dalam penelitian ini adalah siswa Teknik Kendaraan Ringan Sekolah Menengah Kejuruan Nahdlatul Ulama Kaplongan Indramayu sebanyak 276 orang dengan sampel sebanyak 74 orang, teknik pengambilan sampel dengan random sampling. Instrumen penelitian untuk motivasi belajar menggunakan angket dan untuk kebugaran jasmani menggunakan Tes Kebugaran Jasmani Indonesia untuk Sekolah Mengah Atas sederajat.Pengujian hipotesis dengan uji anova dua jalur. Hasil penelitian menyatakan bahwa kebugaran jasmani kelompok siswa yang belajar melalui model pembelajaran taktis lebih baik daripada kebugaran jasmani kelompok siswa yang belajar melalui model pembelajaran langsung dan tidak terdapat interaksi antara model pembelajaran dengan motivasi belajar terhadap kebugaran jasmani.